Uniaxial Compression Creep Relaxation and Grading of Coal Samples via Tests on the Progressive Failure Characteristics. (7th February 2019) - Xiong, Zuqiang; Song, Changsheng; Su, Chengdong; Wang, Xiaolei; Wang, Cheng; Hao, Yu
Abstract : An RMT-150B electrohydraulic servo testing system was used to perform uniaxial compression and uniaxial grading relaxation (creep) tests. The deformation, strength, and failure characteristics of the progressive failure process of coal samples under three loading modes were analyzed. The analysis results show that the prepeak stress-strain curve of the coal samples and the load relationships are not clear and that the whole compression process of coal still showed compression, elastic, yielding, and failure stages. The local stress drop characteristics during our relaxation creep grading tests showed no clear peak value and showed a yield curve with the shape of a conventional single plateau. The values of the mechanical parameters of axial compression were significantly higher than those obtained in the grade relaxation (creep) tests, which showed the mechanical parameters of coal samples with aging characteristics. In the relaxation (creep) tests, when the stress ratio was less than 70%, the relaxation (creep) characteristics of the sample were not clear. When the ratio of stress relaxation (creep) was more than 70% in the relaxation (creep) tests during displacement (stress) with a constant relaxation (creep) over the duration of the test, the evolution, development, and convergence of microcracks in the coal samples were observed. Relaxation (creep) stress was higher, failure duration was shorter, and the duration of failure was longer. For fully mechanized coal faces, increasing the support resistance and timely moving the support after coal cutting may prevent rib spalling accidents by reducing coal stress and exposure time in the front of the working face. Additionally, routine uniaxial compressive failures showed a simple form, having a clear tension-shear dual rupture surface. The staged relaxation creep failure testing of coal is more complex. The entire coal samples were divided into many thin-sheet debris via gradual collapse and shedding, and the number of cracks increased significantly, showing evident lateral expansion characteristics that are similar to the rib spalling characteristics in high coal mining working faces.